345Occupational heat stress and economic burden: evidence to support development of workplace heat management policies. (2nd September 2021) - Borg, Matthew; Bi, Peng; Xiang, Jianjun; Anikeeva, Olga
Abstract: Background: The adverse effects of heat on workers' health and work productivity are well documented. However, the resultant economic consequences and productivity loss are less understood. This review aims to summarize the retrospective and potential future economic burden of workplace heat exposure in the context of climate change. Methods: Literature was searched from database inception to October 2020 using Embase, PubMed, and Scopus. Articles were limited to original human studies investigating costs from occupational heat stress in English. Results: Twenty studies met the criteria. Eighteen studies estimated costs from heat-induced labor productivity loss. Predicted global costs from lost worktime, in US, were 280 billion in 1995, 311 billion in 2010 (≈0.5% of GDP), 2.5 trillion in 2030 (>1% of GDP) and up to 4.0% of GDP by 2100, with additional expenses after considering reduced work efficiency. Three studies estimated heat-related healthcare expenses from occupational injuries with averaged annual costs (US) exceeding 1 million in Spain, 1 million in Guangzhou, China and 250, 000 in Adelaide, Australia. Low- and middle-income countries and countries with warmer climates had greater losses as a proportion of GDP. Greater costs per worker were observed in outdoor industries, amongst males, and workers aged 25 to 44 years. Conclusions: The estimated global economic burden of occupational heat stress is substantial. Climate change adaptation and mitigation strategies should be implemented to likely minimize future costs. Further research exploring the relationship between occupational heat stress and related expenses from lost productivity, decreased work efficiency and healthcare, and costs stratified by demographic factors, is warranted. Key messages: The estimated retrospective and future economic burden from occupational heat stress is large. Responding to climate change is crucial to minimize this burden. Analyzing heat-attributable occupational costs may guide the development of workplace heat management policies and practices as part of global warming strategies.